ECOLOGICAL STRESS AND ITS EFFECTS ON ESSENTIAL HYPERTENSION AND CHRONIC OBSTRUCTIVE BRONCHITIS DEVELOPMENT IN ROSTOV-ON-DON INHABITANTS - L. I. Katelnitskaya; S. A. Shalnova; L. A. Haisheva; S. E. Glova; L. V. Suslova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study prevalence of essential hypertension (HT) and chronic obstructive bronchitis (COB) among Rostov-on-Don population, to assess influence of ecological stress on HT and COB development and to find the ways to improve therapy of combined pathology.Material and methods. Single-stage epidemiologic study of Rostov-on-Don population was carried out. The study included questionnaire to reveal main risk factors of chronic noninfectious diseases, a number of laboratory and instrumental indices.Results. Prevalence of HT and COB is significantly higher in patients, living in ecologically unfavorable districts. Rigidity and stretch ability of vascular wall influence the course and development of HT as well as atrial natriuretic factor. Carbonic anhydrase inhibitor, acetazolamide, when is added to standard therapy increases in its efficacy in blood pressure control, decrease in blood pressure in pulmonary artery and correction of disturbed acidbase balance in patients with HT combined with COB.Conclusion. The connection between unfavorable ecology and HT and COB development is demonstrated. Adjuvant therapy with acetazolamide is proposed to increase in efficacy of HT and COB standard therapy.